Analisis Ex Officio dan Perlindungan Hukum di Pengadilan Agama (Studi Putusan PA Jember Nomor 1323/Pdt.G/2024/PA.Jr) - Yassir, Muhammad; Muthalib, Abd.; Husaini, Akhmad (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2025)
This study aims to examine the role of ex officio authority exercised by judges in the Religious Court, based on Decision Number 1323/Pdt.G/2024/PA.Jr from the Jember Religious Court. The main issue addressed is how the court ensures the protection of women’s and children’s financial rights after divorce, even without a formal request from the wife. The urgency of this study lies in the importance of ensuring substantive justice for vulnerable parties within the Islamic family law system in Indonesia. This research employs a qualitative descriptive-analytical method with a normative juridical approach. Data is collected from legal documents, court decisions, relevant legislation, and academic literature. The analytical technique utilizes an interpretative method with a legal hermeneutic approach to understand the dynamics of ex officio authority application in divorce cases. The study’s findings indicate that the court exercises ex officio authority to determine financial obligations, including iddah maintenance of Rp3,000,000, mut’ah of Rp10,000,000, and child maintenance of Rp1,500,000 per month with an annual increase of 10%. This decision reflects the judge’s proactive role in balancing legal principles and social justice with economic conditions. Additionally, this study analyzes the implications of ex officio decisions in shaping legal precedents in religious courts, particularly in divorce cases. In conclusion, ex officio decisions play a crucial role in achieving justice and protection for vulnerable parties in family law cases. These rulings are not solely based on positive law but also consider substantive justice and the well-being of affected parties. Therefore, the ex officio mechanism can serve as an effective legal instrument in strengthening legal protection for women and children after divorce.